Peran Komunitas Tlasih 87 Sumbergirang Mojokerto dalam Membangun Harmoni Agama - Setiyani, Wiwik (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The article scrutinizes the role of the actor of Tlasih 87 community in coping with social problems and his efforts to create harmony and peace among interreligious adherents in Sumbergirang village of Mojokerto East Java. The writer puts emphasis on the discussion about the methods employed by the actor to achieve his goals. In addition, the form of teaching proposed by the actor to Sumbergirang society will be another focus of the discussion. The writer finds that humanist approach has become the main tool used by the actor of Tlasih 87 in dealing with social problems. Such approach has brought about success to help the marginalized people in Sumbergirang. Regarding the teaching promulgated by the actor of Tlasih 87, the writer argues that this is a sort of cultural and religious syncretism between Javanese and Balinese culture as well as religious teachings of Islam and Hinduism along with kejawen. Although this teaching has encountered challenges during its dissemination, the number of the followers of Tlasih 87 have significantly increased. Tlasih 87 has widely spread out of Sumbergirang in a number of regions in East Java such as Gresik and Surabaya. The main spirit held by the actor of Tlasih 87 is building harmony and creating peace towards the unity of interreligious adherents as well as preserving culture inherited from the past generations.